The Mediating Effects of Place Satisfaction and Support for Community: An Evaluation of the Performance of Small and Medium Tourism Enterprises in Bangladesh - Akter, Mahmoda; Alim, Md. Abdul; Shabbir, Rubaiyat; Ali, Md. Borak; Teck-Weng, Jee; Kasuma, Jati (Asian Journal of Business and Accounting, 2020)
Manuscript type: Research paper Research aims: This study aims to understand the impact of place identity on the performance of small and medium tourism enterprises (SMTEs). It also examines how place satisfaction and support for community mediate the relationship between place identity and the performance of SMTEs. Design/Methodology/Approach: This study focusses on the tourism industry of Bangladesh. Data comprise of 215 small and medium enterprises involved in tourism. Analysis is conducted using the partial least squares-based structural equation modelling (PLS-SEM). Research findings: Results suggest that place identity is related positively to place satisfaction, support for community, and firm performance. Surprisingly, support offered by the firm towards the local community did not contribute to firm performance. In this study, only place satisfaction plays a mediating role between place identity and firm performance. Theoretical contribution/Originality: This study expands on existing literature by providing empirical evidence on the factors that could affect the performance of SMTEs’ tourism business, in the context of Bangladesh. The inconsistency of the relationship between place identity and firm performance may be related to place satisfaction. Practitioner/Policy implication: The findings can be useful for SMTEs, investors, travel agents as well as other stakeholders. Research limitation/Implication: Since this study is focused on the Bangladesh tourism sector alone, the results may not be generalised to other countries.